Ventanillas de Salud (VDS) and Mobile Health Units (MHU): A binational collaborative models - Rangel Gómez, María Gudelia; Salazar, Saúl; López Jaramillo, Ana María; Lira Chávez, Isaura Angélica; Romero Rangel, Alejandra; Caballero Abraham, Martha Leticia; Gutiérrez Reyes, Luis; Rosales, Cecilia B. (Frontiers in Public Health, 2022)
Over the years, the Hispanic/Mexican population living in the United States has faced elevated levels of inequality and disadvantage in terms of health, becoming one of the most vulnerable migrant groups in the country. To help reduce the gaps in health care for the Hispanic/Mexican population, the Mexican government, in collaboration with strategic allies from various sectors, launched the Ventanillas de Salud (VDS) strategy, which was subsequently reinforced through the Mobile Health Units (MHU) care model, to provide culturally adapted, preventive health services to Hispanic/Mexican immigrants in the United States. Both the VDS strategy and the MHU care model are intended to contribute to the development of initiatives, projects, and actions in health that will benefit the Hispanic/Mexican community living in the United States, which lacks or has difficulty accessing health services. This article provides a descriptive, analytical analysis of the VDS strategy and the MHU care model, as unique collaboration models, which can be replicated, and have achieved a positive impact on the health of the Hispanic/Mexican community in the United States, at both the individual and community level.